Co-creating Videogames - Banks, John (Bloomsbury Academic, 2013)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Co-creativity has become a significant cultural and economic phenomenon. Media consumers have become media producers. This book offers a rich description and analysis of the emerging participatory, co-creative relationships within the videogames industry. Banks discusses the challenges of incorporating these co-creative relationships into the development process. Drawing on a decade of research within the industry, the book gives us valuable insight into the continually changing and growing world of video games.